Management of post cleft lip and palate aesthetic defects with bilayered zirconia crowns - a digital approach - Nurani Atikasari; Mefina Kuntjoro; Bambang Agustono; Karina Mundiratri; Harry Laksono; Agus Dahlan; Abil Kurdi; Fatimah Batul; Setyabudi Goenharto (Conservative Dentistry Journal, 2026)
Background: Soft tissue asymmetry, alveolar bone shortage, and anterior tooth loss are common presentations for patients with cleft lip and palate (CLP), which makes restorative rehabilitation more challenging. The cost-effectiveness, accuracy, and time optimisation of digital dental workflows for the production of fixed restorations or prostheses have shown them to be superior to conventional ones. In these situations, achieving both functional stability and aesthetic harmony calls for an all-encompassing, multidisciplinary strategy. Purpose: This report aims to describe the restorative and prosthodontic management of anterior tooth loss in a post-CLP patient using a bilayered zirconia fixed crowns within a fully digital workflow. Case: A 23-year-old female presented with a missing maxillary left lateral incisor (tooth 22) and a history of multiple CLP surgeries, the most recent performed in January 2023. Radiographic evaluation revealed significant alveolar bone resorption (>50%) at the edentulous site. The patient had undergone orthodontic treatment since 2017 but had not received prior restorative and prosthodontic rehabilitation. Case Management: A bilayered zirconia fixed crowns was planned to restore esthetics and function. Pre-treatment procedures included endodontic therapy on tooth 12, intraoral scanning, and diagnostic mock-up. Intraoral digital impressions enabled precise CAD/CAM fabrication. To address Class II gingival recession, 2–3 mm of gingival-colored porcelain was applied to mimic natural soft tissue. A modified ridge lap pontic was designed to optimize hygiene and achieve a lifelike emergence profile. Conclusion: Bilayered zirconia restorations, combined with a digital restorative approach, offer favorable esthetic and functional outcomes in post-CLP anterior rehabilitation.